2002
DOI: 10.1046/j.1365-2168.2002.02263.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide enhances experimental wound healing in diabetes

Abstract: The nitric oxide donor molsidomine can at least partially reverse impaired healing associated with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
140
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(151 citation statements)
references
References 33 publications
8
140
2
1
Order By: Relevance
“…Importantly, cutaneous gene transfer of eNOS or manganese superoxide dismutase was able to restore eNOS expression and NO level, resulting in accelerated wound healing in STZ mice (19). Similarly, application of NO donor molsidomine or NO-releasing poly(vinyl alcohol) hydrogel dressing can partially restore the impaired wound healing in STZ rats (26). These studies indicate that impairment of cutaneous NO function is an important contributor to wound healing delay in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Importantly, cutaneous gene transfer of eNOS or manganese superoxide dismutase was able to restore eNOS expression and NO level, resulting in accelerated wound healing in STZ mice (19). Similarly, application of NO donor molsidomine or NO-releasing poly(vinyl alcohol) hydrogel dressing can partially restore the impaired wound healing in STZ rats (26). These studies indicate that impairment of cutaneous NO function is an important contributor to wound healing delay in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 76%
“…Consistently, dysfunction of cutaneous NO is involved in impaired wound healing. Recent studies including ours have shown that both eNOS expression and NO level were declined in STZ-induced diabetes (19,26). Importantly, cutaneous gene transfer of eNOS or manganese superoxide dismutase was able to restore eNOS expression and NO level, resulting in accelerated wound healing in STZ mice (19).…”
Section: Discussionmentioning
confidence: 97%
“…In diabetic wound healing, a physiologic state consistent with decreased nitric oxide (NO) levels results, leading to an impaired inflammatory response, decreased collagen production, and decreased wound-breaking strength (Witte et al, 2002). Prior studies have also revealed the MMP levels are significantly elevated in chronic diabetic wounds, thus creating an imbalance in matrix breakdown and release of growth factors that are important for normal wound healing (Wysocki et al, 1993;Trengove et al, 1999;Lobmann et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Impaired healing of diabetic wounds is thought to be related to diminished NO production (Witte et al, 2002;Schaffer et al, 1997). Because the level of NO in chronic wounds is low, and elevation of NO enhances wound healing, a number of other approaches have been tried to deliver NO therapeutically.…”
Section: Resultsmentioning
confidence: 99%
“…These agents have been studied in vitro, in airway and gastric epithelial wounds [3,4], and in vivo, in diabetic ulcers [5], and skin abscesses [6]. Yet, the molecular basis for the effect of NO donors in wound healing is poorly defined, and a better understanding of how NO functions to improve wound healing is needed.…”
Section: Introductionmentioning
confidence: 99%